2010
DOI: 10.1111/j.1365-2842.2010.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion and brain function: mastication as a prevention of cognitive dysfunction

Abstract: Research in animals and humans has shown that mastication maintains cognitive function in the hippocampus, a brain area important for learning and memory. Reduced mastication, an epidemiological risk factor for the development of dementia in humans, attenuates spatial memory and causes hippocampal neurons to deteriorate morphologically and functionally, especially in aged animals. Active mastication rescues the stress-attenuated hippocampal memory process in animals and attenuates the perception of stress in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
1
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(221 citation statements)
references
References 144 publications
(220 reference statements)
7
195
1
18
Order By: Relevance
“…It is important to understand masticatory function, and also parafunction that has crucial effects on whole-body health as well as To see bruxism: an fMRI study S Yılmaz cognitive functions. 18 By the end of the 20th century, non-invasive measurements of brain function were developed. 19 The fMRI technique was first used in a study published in 1991, which showed how a standard MRI scanner can be used to track where oxygenated and deoxygenated blood flows in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand masticatory function, and also parafunction that has crucial effects on whole-body health as well as To see bruxism: an fMRI study S Yılmaz cognitive functions. 18 By the end of the 20th century, non-invasive measurements of brain function were developed. 19 The fMRI technique was first used in a study published in 1991, which showed how a standard MRI scanner can be used to track where oxygenated and deoxygenated blood flows in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal pathogens could provide inflammatory mediators due to daily, transient bacteremias, which in return increase the oxidative stress in Alzheimer's disease (AD) 57 . Animal models have tried to avoid these confounding factors and confirm that introducing poor mastication experimentally or administering a soft diet in mice may inhibit learning and memory performance 53,58,59 . Whether the relationship between mastication and cognition is observational or causal is still under discussion, and evidence of the effect of restorative dental measures is still scarce.…”
Section: Cognitionmentioning
confidence: 99%
“…The transient increase of microglial areas in the CA1 after the increase in occlusal vertical dimension may belong to these acute reactions. Although the underlying mechanisms of the transient increase of microglial area in the CA1 are unclear, possible pathways, such as neuronal and humoral pathways from the oral cavity to the hippocampus, were recently reviewed (Ono et al 2010). One possibility is that the increased plasma corticosterone after increasing the vertical dimension is detected by corticosteroid receptors localized in neurons of the hippocampal formation (Han et al 2005;Galeeva et al 2006;Sarabdjitsingh et al 2009) and that such neurons affect microglia.…”
Section: Discussionmentioning
confidence: 99%